A chromatin signature by the methyltransferase SETD7 orchestrates angiogenic response in diabetic limb ischemia. (3rd October 2022) - Mohammed, S; Gorica, E; Karsay, G; Albiero, M; Ambrosini, S; Akhmedov, A; Spinetti, G; Luscher, T F; Fadini, G P; Ruschitzka, F; Costantino, S; Paneni, F
Abstract: Background: Peripheral artery disease (PAD) is highly prevalent in patients with diabetes (DM) and associates with a high rate of limb amputation and poor prognosis. Surgical and catheter-based revascularization have failed to improve outcome in DM patients with PAD. Hence, a need exists to develop new treatment strategies able to promote blood vessel growth in this setting. Mono-methylation of histone 3 at lysine 4 (H3K4me1) – a specific epigenetic signature induced by the histone methyltransferase SETD7 – favours an open chromatin thus enabling gene transcription. Purpose: To investigate whether SETD7-dependent epigenetic changes modulate angiogenic response in diabetes. Methodology: Primary human aortic endothelial cells (HAECs) were exposed to normal glucose (NG, 5 mM) or high glucose (HG, 25 mM) concentrations for 48 hours. Unbiased gene expression profiling was performed by RNA sequencing (RNA-seq) followed by Ingenuity Pathway Analysis (IPA). In vitro assays, namely cell migration and tube formation were employed to study angiogenic properties in HAECs. SETD7 and H3K4me1 levels were investigated by Western blot and Chromatin immunoprecipitation (ChIP). Pharmacological blockade of SETD7 was achieved by using the highly selective inhibitor (R)-PFI-2. Mice with streptozotocin-induced diabetes were orally treated with (R)-PFI-2 or vehicle and underwent hindlimb ischemia by femoral artery ligation for 14 days. Blood flow recovery was analysed at 30 minutes, 7 and 14 days by laser Doppler imaging. Our experimental findings were also translated in gastrocnemius muscle samples from patients with and without diabetes. Results: RNA-seq in HG-treated HAECs revealed a profound upregulation of the methyltransferase SETD7, an enzyme involved in mono-methylation of lysine 4 at histone 3 (H3K4me1). SETD7 upregulation in HG-treated HAECs was associated with increased H3K4me1 levels as well as with impaired endothelial cell migration and tube formation. Both SETD7 gene silencing and pharmacological inhibition by (R)PFI-2 rescued hyperglycemia-induced impairment of HAECs migration and tube formation, while SETD7 overexpression blunted the angiogenic response. RNA-seq and ChIP assays showed that SETD7-dependent H3K4me1 regulates the transcription of the angiogenesis inhibitor semaphorin-3G (SEMA-3G). Moreover, SEMA-3G overexpression blunted migration and tube formation in SETD7-depleted HAECs. In diabetic mice with hindlimb ischemia, treatment with (R)-PFI-2 improved limb vascularization and perfusion as compared to vehicle. Finally, SETD7/SEMA3G axis was upregulated in muscle specimens from T2D patients as compared to controls. Conclusion: Targeting SETD7 represents a novel epigenetic-based therapy to boost neovascularization in diabetic patients with PAD. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University of Zurich - Forshungskredit candoc grant